Physiological basis of acute care - Yoo, Kuen Chan; Kwee, Peng Ng (Elsevier, 2012)
The aim of this book is to simplify physiological principles in a logical manner and provide important and relevant content to help care providers better manage their acutely ill patients. First time learners as well as health care professionals needing a short refresher course in physiology will find simple, easy-to-understand, basic physiology that is relevant to both the student and the professional care provider. With a focus on the importance of good oxygen delivery as the basis of sustaining life, this book links the fabric of life together and enables readers to apply the principles of.